Proses Munculnya Euro-Islam sebagai Transnational Norms di kalangan Muslim Eropa - Mochamad Faisal Karim (Jurnal Kajian Wilayah, 2010)
The study focuses on the formation process of Euro-Islam as a transnational norm among European Muslim to integrate Muslim into European society. There is a growing norm among the European Muslim society called as Euro-Islam norm. In this research, I use norm life cycle theory, brought by Martha Finnemore and Kathryn Sikkink to assess the process of formation of Euro-Islam norm. Although Euro-Islam has not yet entered the stage of internalization norm, I argue that Euro-Islam gradually forms a norm which theoretically will become a base for the formation of future Euro-Islam identity among European Muslim.Keywords: Euro-Islam, Norm, integration, identity